On the Creative Contribution of V. S. Korolyuk to the Development of Probability Theory - Bratiichuk, N. S.; Gusak, D. V.; Svishchuk, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a brief survey of the main results obtained by V. S. Korolyuk in probability theory and mathematical statistics.